Impersonal Forms in Standard Veps - Polina Oskolskaia (Linguistica Uralica, 2024)
The article examines the use of impersonal forms in Modern Standard Veps. In modern Veps dialects, there is a contamination of impersonal forms and 3pl forms: impersonal forms are used in 3pl contexts or, vice versa, 3pl forms are used in impersonal contexts. The current Standard Veps grammar proposes distinguishing impersonal from personal forms, i.e. to use impersonal forms exclusively in impersonal contexts and personal forms in personal contexts. As a result, in the Veps texts, that are supposed to follow the standard rules, the phenomenon from dialects also occurs. The situation where an impersonal form displaces a personal form and is used in the context of 3pl occurs 2.3 times more often than the opposite situation where a personal form appears in an impersonal context. Negative forms are twice as likely to be deviant than affirmative forms.